The Impact of The European Union's Environmental Policy towards Competitiveness in Malaysia's Palm Oil Industry. Issue 1 (1st November 2022) - Othman, N; Yusop, Z; Huay, C S; Azhar, N A Z M
Abstract : Palm oil can't be isolated from the environment and sustainability issues. The consumption of edible palm oil has decreased in recent years due to increased environmental problems. Unfortunately, palm oil has also been portrayed negatively by some groups who claim that palm oil production would cause higher global GHG emissions than conventional fossil fuels due to the conversion of forests and peatlands. The European Union has aimed to increase its use of renewable energy from biofuels, with one of the potential feedstock being palm oil. However, European countries appear to have the most stringent requirement on certified palm oil despite such pros. The growing environmental and sustainability concerns of oil palm farming may adversely affect palm oil's import demand and hence the Malaysian economy. Therefore, the objective of this study is to investigate the effect of environmental policy on Malaysia's competitiveness in palm oil products. The relative trade advantage (RTA) index is used to measure the competitiveness index, and the dynamic generalized method of moment (DGMM) is employed in the study. The data used for this study spans from 2009 to 2016. The results indicate that environmental regulations in the EU positively impact palm oil industry competitiveness, which is technically consistent with the Porter Hypothesis, which argues that more stringent environmental regulations can trigger innovation that may offset the costs of complying among the producers. The progress of palm oil downstream is crucial to improving the overall competitiveness of the palm oil industry and the national economy. As per the findings of this study, the Malaysian government should implement appropriate environmental intervention models to meet international standards. Environmental protection, in general, necessitates significant capital expenditure and long-term investment decisions to fund innovation, which may offset the costs of regulatory compliance and eventually improve trade competitiveness, particularly in the downstream industry.